The Impact of Competency and Professionalism on Audit Quality - Dedy Sudarmadi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
Audit quality is a service that is difficult to measure objectively and is a complex and difficult concept to understand, so that there may be errors in determining its nature and quality. In an audit examination, the auditor must frequently interact or interact with management, this is done to obtain the evidence required in the audit examination. The attitude of the auditor is to recognize the need for an objective assessment of the conditions under investigation and the evidence obtained during the audit. This is done by the auditor so that the audited company's financial statements can be relied on and management will also get confidence and trust from outside parties that management has carried out its responsibilities properly.